A Quality control study on 3M Phiippines, Inc. - Cerrero, Geraldine T. (College of Engineering, 1999)
3M Philippines, a part of a multi-national company, manufactures printed box-sealing tapes, flexible adhesives, contact cements, floor finish chemicals, rubbing compounds, underseal, and traffic control materials. One of the company's manufacturing facilities, which produces job-ordered print tapes is the Printing, Coating and Converting (PCC) Section. This study focused on the quality system of this particular section. Using Statistical Process Control in the analysis of nonconformity and quality performance of products, it was identified that adhesive application process is the most critical process wherein incomplete adhesive occurs. It was ascertained that incomplete adhesive the most significant nonconformity, is a product of an out-of-control process, which is adhesive application. To achieve the objectives of this study, the following corrective actions are recommended: (1) design of experiment to determine the ideal setting of platten temperature, (2) continual monitoring and removal of the accumulated adhesive on the sides before it can cause production stoppages, and (3) regular monitoring of the critical parts of the machine that needs to be replaced. Areas for further study include (1) establishment of standard time for adhesive to melt before the operators can re/start production, (2) investigation of the factors that contribute to the leakage problem in the adhesive applicator, and (3) determination of ideal setting for the hose and gun temperature.